The Presentation of Self in Everyday Life - Goffman Erving (Penguin Books, 1969)
An analysis of the structures of social encounters from the perspective of the dramatic performance. Preface, Acknowledgements, Introduction, Performances, Teams, Regions and Region Behavior, Discrepant Roles, Communication Out of Character, The Arts of Impression Management, Conclusion, Index.